Sidetracked - Asher, Diana Harmon (Amulet Books, 2018)
Joseph Friedman has attention deficit disorder and spends most of his time avoiding the school bully and hiding in the Resource Room. On the first day of seventh grade, however, everything changes: his Resource Room teacher forces him to join the school track team and he meets Heather, a runner who doesn't let herself be pushed around.